Trigo Roller Coasters

Geometry Level 3

Given that S n = k = 1 n tan 1 1 k ( k + 1 ) + 1 \displaystyle S_{n}=\sum_{k=1}^{n} \tan^{-1} \cfrac{1}{k(k+1)+1} for positive integers n N n\in N , evaluate 1 + n = 1 62 1 + tan S n 1 tan S n \displaystyle 1+\sum_{n=1}^{62}\cfrac{1+ \tan S_{n}}{1- \tan S_{n}} .

This is part of the set Fun With Problem-Solving .


The answer is 2016.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Donglin Loo
May 25, 2018

S n = k = 1 n tan 1 1 k ( k + 1 ) + 1 S_{n}=\sum_{k=1}^{n} \tan^{-1} \cfrac{1}{k(k+1)+1} .

S n = k = 1 n tan 1 1 k ( k + 1 ) 1 + 1 k ( k + 1 ) S_{n}=\sum_{k=1}^{n} \tan^{-1} \cfrac{\cfrac{1}{k(k+1)}}{1+\cfrac{1}{k(k+1)}} .

S n = k = 1 n tan 1 1 k 1 k + 1 1 + 1 k ( k + 1 ) S_{n}=\sum_{k=1}^{n} \tan^{-1} \cfrac{\cfrac{1}{k}-\cfrac{1}{k+1}}{1+\cfrac{1}{k(k+1)}} .

S n = k = 1 n ( tan 1 1 k tan 1 1 k + 1 ) S_{n}=\sum_{k=1}^{n} (\tan^{-1}\cfrac{1}{k}-\tan^{-1}\cfrac{1}{k+1}) .

S n = tan 1 1 1 tan 1 1 2 + tan 1 1 2 tan 1 1 3 + . . . + tan 1 1 n 1 tan 1 1 n + tan 1 1 n tan 1 1 n + 1 S_{n}=\tan^{-1}\cfrac{1}{1}-\tan^{-1}\cfrac{1}{2}+\tan^{-1}\cfrac{1}{2}-\tan^{-1}\cfrac{1}{3}+...+\tan^{-1}\cfrac{1}{n-1}-\tan^{-1}\cfrac{1}{n}+\tan^{-1}\cfrac{1}{n}-\tan^{-1}\cfrac{1}{n+1}

S n = tan 1 1 tan 1 1 n + 1 = π 4 t a n 1 1 n + 1 S_{n}=\tan^{-1}{1}-\tan^{-1}\cfrac{1}{n+1}=\cfrac{\pi}{4}-tan^{-1}\cfrac{1}{n+1}

1 + n = 1 62 1 + tan S n 1 tan S n \therefore 1+\sum_{n=1}^{62}\cfrac{1+\tan S_{n}}{1-\tan S_{n}}

= 1 + n = 1 62 tan ( π 4 + S n =1+\sum_{n=1}^{62}\tan (\cfrac{\pi}{4}+S_{n} )

= 1 + n = 1 62 tan ( π 4 + π 4 t a n 1 1 n + 1 ) =1+\sum_{n=1}^{62}\tan (\cfrac{\pi}{4}+\cfrac{\pi}{4}-tan^{-1}\cfrac{1}{n+1})

= 1 + n = 1 62 tan ( π 2 t a n 1 1 n + 1 ) =1+\sum_{n=1}^{62}\tan (\cfrac{\pi}{2}-tan^{-1}\cfrac{1}{n+1})

= 1 + n = 1 62 cot ( t a n 1 1 n + 1 ) =1+\sum_{n=1}^{62}\cot (tan^{-1}\cfrac{1}{n+1})

= 1 + n = 1 62 1 tan ( t a n 1 1 n + 1 ) =1+\sum_{n=1}^{62}\cfrac{1}{\tan (tan^{-1}\cfrac{1}{n+1})}

= 1 + n = 1 62 1 1 n + 1 =1+\sum_{n=1}^{62}\cfrac{1}{\cfrac{1}{n+1}}

= 1 + n = 1 62 ( n + 1 ) =1+\sum_{n=1}^{62}(n+1)

= 1 + ( 2 + 3 + . . . + 63 ) =1+(2+3+...+63)

= 63 64 2 =\cfrac{63\cdot64}{2}

= 2016 =2016

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...